PERAN IBU SINGLE PARENT DALAM MENGEMBANGKAN KOMUNIKASI INTERPERSONAL REMAJA DI DESA SUMBER AGUNG KECAMATAN MEPANGA KABUPATEN PARIGI MOUTONG - Ponisih, Alkomariyah; Pettalongi, Adawiyah; Rus’an, Rus’an (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2022)
This research was conducted in Sumber Agung Village, Mepanga District, Parigi Moutong Regency with the aim of examining the role of single parent mothers in developing interpersonal communication for their teenage children. This study uses qualitative methods, namely by using data collection techniques through direct observation of the object to be studied, interviews (interviews), and documentation by looking at the final results. The data analysis technique that the author uses is data reduction, data presentation, and drawing conclusions. Based on the results of this study, it was shown that (1) the role of single parent mothers in developing adolescent interpersonal communication in Sumber Agung Village, Kec. Mepanga Kab. Parigi Moutong is already good but still not effective in educating and dividing time in supervising their children. (2) The obstacles commonly faced by single parents are being busy at work because being a Single Parent must be able to play a dual role in working to meet family needs, emotions are not stable sometimes children Teenagers are still emotionally unstable, busy with their world and the environment is not good, making it a little difficult for Single Parent mothers to deal with their teenage children.